DNA methylation patterns of candidate genes regulated by thymine DNA glycosylase in patients with TP53 germline mutations - Fortes, Fernanda Paschoal; Kuasne, Hellen [UNESP]; Marchi, Fabio Albuquerque; Miranda, Priscila Mayrink; Rogatto, Silvia Regina [UNESP]; Achatz, Maria Isabel (Assoc Bras Divulg Cientifica, 2015)
Li-Fraumeni syndrome (LFS) is a rare, autosomal dominant, hereditary cancer predisposition disorder. In Brazil, the p.R337H TP53 founder mutation causes the variant form of LFS, Li-Fraumeni-like syndrome. The occurrence of cancer and age of disease onset are known to vary, even in patients carrying the same mutation, and several mechanisms such as genetic and epigenetic alterations may be involved in this variability. However, the extent of involvement of such events has not been clarified. It is well established that p53 regulates several pathways, including the thymine DNA glycosylase (TDG) pathway, which regulates the DNA methylation of several genes. This study aimed to identify the DNA methylation pattern of genes potentially related to the TDG pathway (CDKN2A, FOXA1, HOXD8, OCT4, SOX2, and SOX17) in 30 patients with germline TP53 mutations, 10 patients with wild-type TP53, and 10 healthy individuals. We also evaluated TDG expression in patients with adrenocortical tumors (ADR) with and without the p.R337H TP53 mutation. Gene methylation patterns of peripheral blood DNA samples assessed by pyrosequencing revealed no significant differences between the three groups. However, increased TDG expression was observed by quantitative reverse transcription PCR in p.R337H carriers with ADR. Considering the rarity of this phenotype and the relevance of these findings, further studies using a larger sample set are necessary to confirm our results.
Keywords: Li-Fraumeni syndrome; TP53 gene; TDG; Methylation